2011
DOI: 10.1007/s11095-010-0350-0
|View full text |Cite
|
Sign up to set email alerts
|

Data Requirements for the Reliable Use of Atomic Pair Distribution Functions in Amorphous Pharmaceutical Fingerprinting

Abstract: The ambiguities make data measured using low energy x-rays unsuitable for fingerprinting active pharmaceutical ingredients and small molecule systems, and, in general, copper anode diffractometers are undesirable for this purpose; however, laboratory x-ray sources with either Mo or Ag anodes are well suited for this application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 17 publications
2
87
0
Order By: Relevance
“…19 A recent investigation into the minimum energies necessary to study amorphous pharmaceutical compounds found that there is not enough information in data collected on CALS diffractometers for reliable fingerprinting analysis. 11 However, MALS and SALS diffractometers and synchrotrons are capable of producing sufficiently information-rich PDFs. 11 Sample Preparation and Characterization.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…19 A recent investigation into the minimum energies necessary to study amorphous pharmaceutical compounds found that there is not enough information in data collected on CALS diffractometers for reliable fingerprinting analysis. 11 However, MALS and SALS diffractometers and synchrotrons are capable of producing sufficiently information-rich PDFs. 11 Sample Preparation and Characterization.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…44,46,47 Strong evidence also exists, that to this picture must be added a second order parameter arising from a tendency of such homogeneous preferred arrangements to be altered by localized bond orientational order, particularly as the liquid is cooled below T m into the supercooled and glassy states. 23 Such localized orientational order can arise from preferred geometric packing arrangements as with fragile more nonpolar liquids, as well as from specific directional hydrogen bonding and tetrahedral covalent arrangements, as in strong liquids such as inorganic oxides, for example, SiO 2 .…”
Section: Liquid and Amorphous Solid Structurementioning
confidence: 99%
“…using CuK radiations) may be used [8], however the PDF obtained are relatively featureless and dominated by spurious effects from the Fourier transform or poor normalization, which can lead to misinterpretations of the data. It is thus more favorable to use shorter wavelength radiations for PDF analysis [9]. Note that the angular 01003-p. 5 EPJ Web of Conferences resolution of the diffractometer is less restrictive, though too low resolution in reciprocal space leads to a rapid decrease of the PDF intensity with distance in direct space.…”
Section: How To Measure the Pdfmentioning
confidence: 99%
“…Here, several peaks corresponding to well identified pairs of atoms can be observed, either because they are isolated (the first 3 peaks) or because they strongly dominate the PDF (the Pb-Pb peaks). Although they correspond to interatomic distances in a crystalline phase, these peaks clearly 01003-p. 9 EPJ Web of Conferences have a finite width. This width is due to the distribution of distances for the given atomic pair, due to thermal displacements and static disorder.…”
Section: The Pdf Peak Widthmentioning
confidence: 99%